(untitled) (Interdisciplinary Studies Journal, 2025)
This paper presents a proposal for a didactic sequence for the development of classes for the second year of high school, adopting the theme of climate change. A search for scientific data that serve as a basis for the problem of climate change is carried out and from the data collected by the teacher and by the students themselves, a large group discussion is held, aiming to establish a relationship between such data and mathematics, as well as a social and political awareness on the subject. It aims to promote the debate on climate change, connected with the episode of floods that occurred in Rio Grande do Sul, in the years 2023 and 2024. Students are expected to understand the basics of statistics and be able to use them to interpret information pertaining to climate data.